1961
DOI: 10.1002/aic.690070239
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic effectiveness factor under nonisothermal conditions

Abstract: The effectiveness factor for a poroussolid-catalyzed reaction is a measure of the extent to which species transport by Knudsen diffusion within the particle retards the over-all rate process. The literature reveals correlations based upon analytical solution of the appropriate equations when isothermal conditions prevail throughout the catalyst particle. Following Thiele's original work ( 5 ) , Wheeler (8) and Weisz (7) have made significant contributions to the discussion of the isothermal effectiveness fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

1969
1969
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 4 publications
2
50
0
1
Order By: Relevance
“…The onset of diffusion limited regimes can be altered by changing the reactor design, the catalyst pore structure, the catalyst particle size, and the distribution of the active sites in the catalyst particles. Values of various dimensionless groups can be calculated to estimate the extents to which transport phenomena may control catalytic performance for specific operating conditions [23][24][25][26][27][28][29][30][31]; however, these calculations are most reliable for cases where the intrinsic reaction kinetics are known. In these cases, it is possible to make catalysts with structures designed to provide adequate rates of diffusion and yet offering high surfaces areas, leading to high rates of reaction per reactor volume, such as the design of specific pore size distributions (e.g., bimodal distributions containing large pores leading to high accessibility of the active sites within the interior of the catalytic pellet, and small pores that branch from the larger pores leading to high surface areas), the formulation of unique pellet shapes (that lead to high accessibility of the active sites but do not cause large pressure drops through the catalytic reactor), and the synthesis of catalyst pellets containing a spatial distribution of the active material within the catalyst pellet [32].…”
Section: Desired Characteristics Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of diffusion limited regimes can be altered by changing the reactor design, the catalyst pore structure, the catalyst particle size, and the distribution of the active sites in the catalyst particles. Values of various dimensionless groups can be calculated to estimate the extents to which transport phenomena may control catalytic performance for specific operating conditions [23][24][25][26][27][28][29][30][31]; however, these calculations are most reliable for cases where the intrinsic reaction kinetics are known. In these cases, it is possible to make catalysts with structures designed to provide adequate rates of diffusion and yet offering high surfaces areas, leading to high rates of reaction per reactor volume, such as the design of specific pore size distributions (e.g., bimodal distributions containing large pores leading to high accessibility of the active sites within the interior of the catalytic pellet, and small pores that branch from the larger pores leading to high surface areas), the formulation of unique pellet shapes (that lead to high accessibility of the active sites but do not cause large pressure drops through the catalytic reactor), and the synthesis of catalyst pellets containing a spatial distribution of the active material within the catalyst pellet [32].…”
Section: Desired Characteristics Of Amentioning
confidence: 99%
“…In some cases, transport effects can be used to improve the selectivity of a catalyst, such as in the case of shape-selective catalysis in zeolites [33][34][35][36]. In the following sections, we focus on various factors controlling the intrinsic reaction kinetics of catalysts, and we refer the reader to other articles for further discussion on transport effects in heterogeneous catalysis [23][24][25][26][27][28][29][30][31].…”
Section: Desired Characteristics Of Amentioning
confidence: 99%
“…The problem was subsequently approached numerically by, among others, Carberry,8 who examined first and second order kinetics in a catalyst of slab geometry, and Weisz and Hicks, 9 who considered first order kinetics in a spherical catalyst particle. Both these studies presented results for the effectiveness factor as a function of the Thiele modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Carberry (6) has shown that this is not a bad approximation if 6 < 6, and Liu (12) restricts himself to this range. However, this excises a large part to the range of nonuniqueness which is under consideration here.…”
Section: (4)mentioning
confidence: 94%